Numerical Simulation of the Motion of Inextensible Capsules in Shear Flow Under the Effect of the Natural State (Communications in Computational Physics, 2018)
In this paper, a computational model for the natural state of an inextensiblecapsule has been successfully combined with a spring model of the capsule membraneto simulate the motion of the capsule in two-dimensional shear flow. Besides the viscosityratio of the internal fluid and external fluid of the capsule, the natural state alsoplays a role for having the transition between two well known motions, tumbling andtank-treading (TT) with the long axis oscillates about a fixed inclination angle (a swingingmode), when varying the shear rate. Between tumbling and tank-treading, theintermittent behavior has been obtained for the capsule with a biconcave rest shape.The estimated critical value of the swelling ratio for having the intermittent transitionbehavior is less than 0.7, i.e., the capsules with rest shape closer to a full disk do nothave the intermittent behavior in shear flow. The intermittent dynamics of the capsulein the transition region is a mixture of tumbling and TT with a swinging mode. Justlike the motion of TT with a swing mode, which can be viewed as a tank-treading withan incomplete tumbling, the membrane tank-treads backward and forward within asmall range during the tumbling motion.